Islamic mobile banking smart services adoption and use in Jordan - Saad Ghaleb Yaseen; Ihab Ali El Qirem; Dima Dajani (ISRA International Journal of Islamic Finance, 2022)
Purpose - The research identifies the predictors of Islamic mobile banking (IMB) smart services adoption and usage in Jordan. Design/methodology/approach - Based on the Unified Theory of the Acceptance and Use of Technology (UTAUT) and the Unified Theory of the Acceptance and Use of Technology 2 (UTAUT2), an extended and modified model that encompasses perceived trust was developed. The sample comprised 358 customers from Islamic banks (IBs) in Jordan, and structural equation modelling was applied to examine data drawn from the sample. Findings - The research framework presented 0.728% of the behavioural intention variance and 0.455% of the use behaviour. Results discovered that performance expectancy, perceived trust and hedonic motivation have significant relations with behavioural intention. The finding that effort expectancy has an insignificant effect and that social influence has a significant negative influence on behavioural intention was unexpected. Research limitations/implications - The research has successfully verified the effect of performance expectancy, perceived trust and hedonic motivation on the customer's intention to use IMB smart services. However, the research data findings are based on the cross-sectional design. Practical implications - The outcomes hold implications for marketing strategy makers who are responsible for promoting IMB smart services in IBs. Originality/value - This research presents a deeper insight into IMB adoption and use. The research employed UTAUT and UTAUT2 as the baseline model and incorporates perceived trust to estimate behavioural intention. To the best of the authors' knowledge, this could be the first inquiry that examines IMB smart services adoption and use in Jordan.
Keywords: 330; Behavioural intention; Islamic banks; Islamic mobile banking adoption; Smart services